Regulation of Intrinsic Functions of PD-L1 by Post-Translational Modification in Tumors - Nihira, Naoe Taira; Miki, Yoshio (Frontiers in Oncology, 2022)
Tumor cells are eliminated by the immune system, including T lymphocytes and natural killer cells; however, many types of tumor cells acquire the immune tolerance by inhibiting T-cell activation and functions via immune checkpoint molecules. Immunotherapy targeting immune checkpoint molecules such as Programmed death receptor 1 (PD-1)/Programmed death ligand 1 (PD-L1) and cytotoxic T lymphocyte associated protein 4 (CTLA-4) have shown successful outcomes for multiple cancer treatments, however some patients show the lack of durable responses. Thus, discovering the chemical compounds or drugs manipulating the expression or function of immune checkpoint molecules are anticipated to overcome the drug resistance of immune checkpoint inhibitors. Function of inhibitory immune checkpoint molecules is often dysregulated by the transcriptional and post-translational levels in tumors. Here, this review focuses on the post-translational modification of intrinsic PD-L1 functions and regulators for PD-L1 transcription.